Writing Compare and Contrast Essay : An Error Analysis in Punctuation ( A case study at Nasional Pasim University, Bandung) - Siti Sopiah (Jurnal Sastra - Studi Ilmiah Sastra, 2019)
Writing needs macro and micro skills (Ur, 1996). Punctuation belongs to the micro  skill. Although, punctuation tends to be considered light in writing, the researcher still found that some students still made an error in placing proper punctuation to their English writing. Therefore, to obtain valid data, a study to investigate the issue needs to be conducted. This research tried to study errors in punctuation that students made in writing compare and contrast essay at Nasional Pasim University. The participants are twenty accounting students who were taking English Writing class. The study shows the largest percentage of error in punctuation mark is Comma. From total errors in punctuation, the percentage of comma remains 56 % in test 1 and 46 % in test 2. Meanwhile, Period is 51 % in first test 1 and 36% in test 2. Parentheses is 40% in test 1 and 1 % in test 2. Meanwhile, Apostrophe shows 11 % in test 1 and 15 % in test 2. Other punctuation mark places 4. 8 %. The data indicates that in writing compare and contrast essay, students tend to commit errors in propering punctuation mark to their writing. Therefore, in teaching writing, micro skills should be considered important as the macro ones by teachers. Students need more explanation on the use of punctuation, especially the use of comma, such as the explanation on transitional devices in which relates to the rules of comma before they practice to write a written product.